Corporate Governance, Profitabilitas, Laverage Dan Penghindaran Pajak: Ukuran Perusahaan Sebagai Variabel Moderasi - Kuni Faizah (Jurnal Sosial Ekonomi Bisnis, 2022)
Objective: This study aims to obtain empirical evidence about the effect of institutional ownership, profitability, leverage on tax avoidance with firm size as a moderating variable. Methods: This study used a sample of Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019. The sampling method used the purposive sampling method and produced 137 data samples. The technique used in this research is multiple regression analysis and absolute difference value analysis for the moderating variable. Findings: The findings in this study that institutional ownership has no effect on tax avoidance, profitability has no effect on tax avoidance, and leverage has a significant negative effect on tax avoidance. Firm size cannot moderate the negative effect of institutional ownership on tax avoidance, firm size cannot moderate the positive effect of profitability on tax avoidance, and firm size cannot moderate the negative effect of leverage on tax avoidance. Novelty: The difference between this research and previous research is that this research tries to integrate several topics regarding the variable of tax avoidance practices which are influenced by three variables, namely institutional ownership, profitability, leverage with firm size.